A PROSPECTIVE RANDOMIZED STUDY TO COMPARE THE EFFICACY OF TWO DIFFERENT DOSES OF INTRAVENOUS DEXMEDETOMIDINE IN ATTENUATING HEMODYNAMIC RESPONSES DURING LARYNGOSCOPY AND ENDOTRACHEAL INTUBATION - SARA MARY THOMAS; HARSH RATHOD; JIGISHA MEHTA; KALPESH PATIL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of this study was to compare the efficacy of two different doses of intravenous dexmedetomidine (0.75 mcg/kg vs. 1 mcg/kg) in attenuating the hemodynamic responses during laryngoscopy and endotracheal intubation in adult patients undergoing elective surgeries under general anesthesia. The study aimed to evaluate the optimal dose that balances effective cardiovascular stabilization with minimal adverse effects. Methods: This prospective randomized study included 60 adult patients (American Society of Anesthesiologists I and II) aged 18–60 years undergoing elective surgeries under general anesthesia. Patients were randomly allocated into two groups: Group A (n=30) received dexmedetomidine 0.75 mcg/kg IV, and Group B (n=30) received dexmedetomidine 1 mcg/kg IV as an infusion in 100 mL normal saline over 15 min 30 min before induction. Hemodynamic parameters (heart rate [HR], systolic blood pressure, diastolic blood pressure, and mean arterial pressure [MAP]) were recorded at baseline before drug administration, at 15 and 30 min following administration of the study drug until induction, after induction, during laryngoscopy and intubation, and subsequently at 1, 3, 5, and 7 min after intubation. Post-operative sedation was assessed using the Ramsay Sedation Score. Results: Both groups showed significant attenuation of hemodynamic responses during laryngoscopy and endotracheal intubation. Group B (1 mcg/kg) demonstrated significantly better control of HR and blood pressure during laryngoscopy and intubation compared to Group A (0.75 mcg/kg). The mean percentage increase in HR from baseline during laryngoscopy and intubation was 11.8±3.2% in Group A compared to 5.8±2.0% in Group B (p<0.001). Similarly, the mean percentage increase in MAP was 9.7±2.8% in Group A versus 4.5±1.8% in Group B (p<0.001). Group B showed a higher incidence of bradycardia (20.0% vs. 6.7%) and hypotension (10.0% vs. 0.0%) compared to Group A, though these were easily managed. Post-operative sedation scores were significantly higher in Group B for the first 90 min after extubation. Conclusion: Dexmedetomidine at a dose of 1 mcg/kg IV provides more effective attenuation of hemodynamic responses to laryngoscopy and endotracheal intubation compared to 0.75 mcg/kg. However, it is associated with a higher incidence of bradycardia and hypotension, requiring vigilant monitoring. The choice of dose should be individualized based on the patient’s cardiovascular status and clinical requirements.